2009
DOI: 10.1007/s00280-009-1050-5
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide in malignant gliomas: current use and future targets

Abstract: Temozolomide (TMZ) is an oral alkylating agent that is regarded as a tolerable and effective drug. When combined with radiotherapy in patients with newly diagnosed glioblastoma, survival is significantly prolonged. This finding has led to widespread use of TMZ for patients with this disease. We summarize developing concerns regarding the use of TMZ, imaging of malignant gliomas, and the pharmacology of TMZ-mechanism of action, scheduling and strategies for overcoming resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
143
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(145 citation statements)
references
References 56 publications
0
143
0
2
Order By: Relevance
“…At physiologic pH, it undergoes rapid chemical conversion to methyl-triazeno-imidazole-carboxamide, the active drug. 28 This exerts its cytotoxic effect through methylation of deoxyribonucleic acid (DNA) at the O 6 position of guanine, 29 which then mispairs with thymine during the next cycle of DNA replication. The sequence of mismatch-repair events initiated leads to apoptosis.…”
Section: Temozolomidementioning
confidence: 99%
“…At physiologic pH, it undergoes rapid chemical conversion to methyl-triazeno-imidazole-carboxamide, the active drug. 28 This exerts its cytotoxic effect through methylation of deoxyribonucleic acid (DNA) at the O 6 position of guanine, 29 which then mispairs with thymine during the next cycle of DNA replication. The sequence of mismatch-repair events initiated leads to apoptosis.…”
Section: Temozolomidementioning
confidence: 99%
“…Although surgery followed by chemotherapy is the normal treatment regimen for gliomas, most malignant gliomas are resistant to chemotherapeutic agents. Because the blood-brain barrier (BBB) restricts and regulates the delivery of chemotherapy agents, the prognosis for glioma is poor (Stupp et al, 2007;Villano et al, 2009). Therefore, it is necessary to develop highly permeable agents that cross the BBB for the chemotherapeutic treatment of patients with malignant glioma.…”
Section: Introductionmentioning
confidence: 99%
“…To date, a number of methods have been described to inhibit MGMT; however, their significance in clinical use for the purpose of overcoming temozolomide resistance is still limited or unknown [3,37,38]. Here, we have shown that the molecular pathway linking MEK to MGMT expression could offer novel and rational targets for MGMT inactivation, specifically MEK (by SL327) and MDM2 (by Nutlin-3).…”
Section: Resultsmentioning
confidence: 88%
“…The standard of care for glioblastoma is composed of maximal surgical resection followed by radiotherapy with concomitant and adjuvant chemotherapy [1,2]. Temozolomide is a monofunctional alkylating agent currently used as the first-line chemotherapeutic agent against newly diagnosed glioblastoma and is also a drug of choice for recurrent disease [3,4]. Sensitivity of tumor cells to temozolomide is therefore key to successful management of this intractable disease; however, unfortunately glioblastoma cells often exhibit resistance against this alkylating agent.…”
Section: Introductionmentioning
confidence: 99%